Forgiveness as a character strength: Toward a developmental model and research agenda. Issue 3 (3rd July 2022) - Tirrell, Jonathan M.
ABSTRACT: Forgiveness involves a shift from negative thoughts, emotions, and behaviors to positive ones after a transgression. Previous research supports the benefits of forgiving, particularly for physical and emotional health. However, debates within the character development literatures exist regarding whether forgiveness is a strength that benefits all parties involved in the transgression. For example, forgiveness is often linked to pardoning, condoning, or justifying bad behavior and forswearing justice. Nietzsche regarded forgiveness as a weakness, and as an undesirable attribute or vice; Gandhi, however, believed forgiveness reflected good moral character and virtuous behavior. I propose a relational developmental systems (RDS)-based model of forgiveness as a character strength that benefits both individuals and contexts following a transgression. I situate forgiveness within RDS metatheory and character development and assess forgiveness across two contexts: school bullying and criminal behavior. Implications for research, education, and intervention promoting adaptive social relationships and thriving are discussed.